North-South Imbalances in the International Trade Regime: Why the WTO Does Not Benefit Developing Countries as Much as it Could - Bernhardt, Thomas (Consilience, 2014)
Participation in international trade potentially brings huge benefits to developing countries. However, the design and setup of the international trade regime, most importantly the rules and regulations stipulated in the agreements of the World Trade Organization (WTO), often make it difficult for developing countries to fully tap this potential. As will be argued in this paper using descriptive statistics, some of these agreements lead to imbalanced consequences for developing vs. developed countries. First, one of the key objectives of WTO agreements, namely to enhance member states access to other members markets, has so far been realized in a rather imbalanced fashion, to the detriment of developing countries. Second, various WTO stipulations contribute to reducing the “policy space” of developing countries, thereby hampering their ability to pursue national policies aimed at fostering economic development. A lot of this can be related to asymmetries in the governance structure of the WTO which help explain why international trade negotiations have preserved such imbalanced outcomes. Against this backdrop, this paper advocates for a pro-development international trade regime that facilitates a more sustainable integration of developing countries into the world economy and that supports their efforts to fully reap the benefits that participating in the international division of labor offers to them.